2008
DOI: 10.1111/j.1365-313x.2008.03642.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective mRNA translation coordinates energetic and metabolic adjustments to cellular oxygen deprivation and reoxygenation in Arabidopsis thaliana

Abstract: SummaryCellular oxygen deprivation (hypoxia/anoxia) requires an acclimation response that enables survival during an energy crisis. To gain new insights into the processes that facilitate the endurance of transient oxygen deprivation, the dynamics of the mRNA translation state and metabolites were quantitatively monitored in Arabidopsis thaliana seedlings exposed to a short (2 h) or prolonged (9 h) period of oxygen and carbon dioxide deprivation and following 1 h of re-aeration. Hypoxia stress and reoxygenatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
406
2
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(452 citation statements)
references
References 66 publications
(85 reference statements)
27
406
2
11
Order By: Relevance
“…The use of the mRNA accumulated in the cell is supported by data showing only a 0.4% increase in total mRNA at 1 h after re-aeration, compared to an increase of more than 50% in mRNAs bound to ribosomes. 12 This result suggests that after the removal of stress, transcripts do not change much quantitatively or qualitatively. The strong growth in translation results from molecular processes leading to the transport of mRNA from the site of storage to the site of protein synthesis.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The use of the mRNA accumulated in the cell is supported by data showing only a 0.4% increase in total mRNA at 1 h after re-aeration, compared to an increase of more than 50% in mRNAs bound to ribosomes. 12 This result suggests that after the removal of stress, transcripts do not change much quantitatively or qualitatively. The strong growth in translation results from molecular processes leading to the transport of mRNA from the site of storage to the site of protein synthesis.…”
Section: Discussionmentioning
confidence: 53%
“…Storing a large amount of non-degraded transcript in the nucleus may be one of the causes of the strong decrease in translation in the absence of changes in the amount of mRNA. 11,12 Although our research shows a strong accumulation of poly (A) RNA in the cell nucleus, it does not concern all examined transcripts. In A. thaliana and Lupinus luteus, the mRNA of ADH1 did not stored in the cell nucleus during hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Recent genome-scale analyses of translation have revealed that translational repression upon salinity stress and the other abiotic stresses can severely restrict gene expression and affect various mRNAs differently. [3][4][5] These findings suggest that global translational repression upon salinity stress is a major mechanism of gene expression control in the plant salinity stress response.…”
mentioning
confidence: 90%